2021
DOI: 10.1159/000514710
|View full text |Cite
|
Sign up to set email alerts
|

Probable Case of Vertical Transmission of SARS-CoV-2 in a Newborn in Mexico

Abstract: <b><i>Background:</i></b> Much remains unknown about the transmission of the SARS-CoV-2 virus. Pregnant women are considered part of the risk population, and vertical transmission of other coronaviruses has been suggested; however, this type of transmission in SARS-CoV-2 is believed to be unlikely. <b><i>Case Report:</i></b> A newborn delivered in term via cesarean section to an asymptomatic but COVID-19-positive 35-year-old woman started with respiratory distres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Both neonates had negative PCR results at 23 and 48 hours, as in our study. Mendoza-Hernández et al 32 reported positive PCR tests in one case taken in the 36th hour after birth in a case with respiratory distress and pneumothorax. Another case, reported by Coronado et al, presented with respiratory distress, fever, cough, and nasal blockage in the 3rd week.…”
Section: Discussionmentioning
confidence: 97%
“…Both neonates had negative PCR results at 23 and 48 hours, as in our study. Mendoza-Hernández et al 32 reported positive PCR tests in one case taken in the 36th hour after birth in a case with respiratory distress and pneumothorax. Another case, reported by Coronado et al, presented with respiratory distress, fever, cough, and nasal blockage in the 3rd week.…”
Section: Discussionmentioning
confidence: 97%
“…Amniocentesis, umbilical cord blood, placenta, neonatal secretions, and breast milk samples were used to determine the vertical transmission of SARS‐CoV‐2 45 . Many investigations have demonstrated that newborn samples delivered by pregnant mothers with various levels of COVID‐19 infection tested positive for SARS‐CoV‐2 polymerase chain reaction (PCR), but perinatal transmission could not be ruled out 45–47 . Latest research findings appear to support this.…”
Section: Transmission Routes Of Sars‐cov‐2mentioning
confidence: 99%
“…45 Many investigations have demonstrated that newborn samples delivered by pregnant mothers with various levels of COVID-19 infection tested positive for SARS-CoV-2 polymerase chain reaction (PCR), but perinatal transmission could not be ruled out. [45][46][47] Latest research findings appear to support this. As immunoglobulin M (IgM) does not penetrate the placental barrier into the fetus, it was hypothesized that the fetus may have been infected with SARS-CoV-2 in utero based on analysis of neonatal blood samples collected 2 h after delivery from a pregnant woman diagnosed with COVID-19.…”
mentioning
confidence: 94%
“…While vertical transmission of the virus has not been observed in an overwhelming number of cases, there is still potential for maternal immune activation [66]. When maternal immune activation occurs, it has been stated that an impact on the developing fetal brain is likely.…”
Section: Potential Adverse Effects On Fetusmentioning
confidence: 99%